ANALISIS KONSEP TEMATIK PADA TAMAN PERUMAHAN DI KOTA BARU PARAHYANGAN SEBAGAI DAYA TARIK BAGI ANAK-ANAK (The Thematic Concept Analysis of the Neighborhood Parks in Kota Baru Parahyangan as an Attraction for Children) - Setiamurti Rahardjo; Andreas Handoyo (Unika Soegijapranata Semarang, 2015)
Neighborhood parks are generally designed as esthetical elements. Nevertheless, some are intentionally designed to become recreational facilities to the residents, especially in a form of playground for children. Kota Baru Parahyangan (KBP) is a residential area with clusters, all of which are complemented by thematic park(s). With each cluster adopts a different theme for its park(s), the implementation of the thematic concept of the park may vary between one cluster and another. Therefore, this paper aims to analyze the implementation of the thematic concept in the neighborhood park design as an attraction for children. It also aims to bring out the park that has applied the this concept most successfully, as a reference for further park design and planning in the residential neighborhood context. The research is performed sequentially which includes: scoring the park facilities in 9 clusters that are already built through a quantitative method, followed by the discussion of the analysis through a qualitative method. As the result, Tatar (cluster) Jingganagara is found as the best cluster that has successfully integrated its thematic concept to the rest of the facilities in the park, and contributed good impacts to the cluster itself and the other clusters nearby.